1980
DOI: 10.1111/j.1533-8525.1980.tb00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Stratification and Male Biography: From Deprivation to Ascendance

Abstract: This essay examines some of the implications of early childhood confinement to the household for the development of male character structure. The argument developed is that assignment to women and the household makes small boys outsiders, who receive less comprehensible and positive forms of socialization than small girls. This deprivation experience contributes to the competitiveness and assertiveness of the male response to more favored treatment during the school years, leading to their eventual ascendance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Specifically, whether reported gender differences in both activity involvement and the factors influencing such involvement remain stable as women and men age is not clear. Developmental research has revealed that patterns of cognitive, moral, and personality or ego development, as well as socialization experiences and cultural expectations differ by gender to various degrees across age (Bleier, 1983;Block, 1973;Gilligan, 1983;Haan, 1972;Hunt, 1980;Loevinger, 1976;Maas & Kuypers, 1975;Neugarten, 1968a;Reinke, 1985;Rodeheaver & Datan, 1985;Rossi, 1980Rossi, , 1984Rothbart & Maccoby, 1966;Sales, 1977;Veroff & Smith, 1985). For example, studies of personality have shown that until about 40 or 50 years of age women tend to score higher on affiliative and relational measures and men, on measures of independence and agency.…”
mentioning
confidence: 96%
“…Specifically, whether reported gender differences in both activity involvement and the factors influencing such involvement remain stable as women and men age is not clear. Developmental research has revealed that patterns of cognitive, moral, and personality or ego development, as well as socialization experiences and cultural expectations differ by gender to various degrees across age (Bleier, 1983;Block, 1973;Gilligan, 1983;Haan, 1972;Hunt, 1980;Loevinger, 1976;Maas & Kuypers, 1975;Neugarten, 1968a;Reinke, 1985;Rodeheaver & Datan, 1985;Rossi, 1980Rossi, , 1984Rothbart & Maccoby, 1966;Sales, 1977;Veroff & Smith, 1985). For example, studies of personality have shown that until about 40 or 50 years of age women tend to score higher on affiliative and relational measures and men, on measures of independence and agency.…”
mentioning
confidence: 96%